192k views
16 votes
2(x - 1) = 4x + 3 explain your answer

User Hythloth
by
5.3k points

2 Answers

8 votes

Answer:

x = -2

Explanation:

2 (x - 1) = 4x + 3

use the distributive property

2x - 2 = 4x + 3

+2 +2

2x = 4x + 5

-4x -4x

-2x = 5

divide by -2

x = - 5/2

User Jannes
by
5.5k points
9 votes

Answer:

Explanation:

Here you go mate߷

Step 1߷

2(x - 1) = 4x + 3 Question߷

Step 2߷

2(x - 1) = 4x + 3 Simplify߷

Step 3߷

2(x - 1) = 4x + 3 Add 2 to sides߷

2x=4x+5߷

Step 4߷

2x=4x+5 subtract 4x from sides߷

-2x=5߷

Step 5߷

-2x=5 Divide sides by -2߷

answer߷

x=-5/2߷

Hope this helps߷

User TrazeK
by
4.6k points